1995
DOI: 10.3950/jibiinkoka.98.642
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Olfactory Disturbance by Endoscopic Endonasal Surgery for Chronic Sinusitis

Abstract: Olfactory disturbance is the one of the most important symptoms of chronic sinusitis.In the present study, we followed up the postoperative clinical course of olfactory disturbance in patients who underwent surgery for chronic sinusitis.Ninety patients with severe olfactory disturbance or anosmia who underwent endoscopic endonasal surgery for chronic sinusitis with severe olfactory disturbance or anosmia in the preceding three-year period were enrolled in this study. We obtained a high postoperative improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, it is now known that endoscopic sinus surgery yields a beneficial outcome for this dysfunction. [1][2][3] To evaluate the effects of surgical intervention on olfaction, the University of Pennsylvania Smell Identification Test consisting of 40 items (UPSIT 40 ) or the T&T olfactometer of 5 odorants (T&T 5 ), a standardized test kit in Japan, is available. Some problems are, however, that T&T 5 is a tedious test procedure and UPSIT 40 demands prolonged concentration by the patient, making these tests less practical in a busy clinic.…”
mentioning
confidence: 99%
“…Furthermore, it is now known that endoscopic sinus surgery yields a beneficial outcome for this dysfunction. [1][2][3] To evaluate the effects of surgical intervention on olfaction, the University of Pennsylvania Smell Identification Test consisting of 40 items (UPSIT 40 ) or the T&T olfactometer of 5 odorants (T&T 5 ), a standardized test kit in Japan, is available. Some problems are, however, that T&T 5 is a tedious test procedure and UPSIT 40 demands prolonged concentration by the patient, making these tests less practical in a busy clinic.…”
mentioning
confidence: 99%
“…Olfactory improvement after endoscopic sinus surgery has been studied by Ohtori et al [39] who noted that younger patients (< 30 years of age) showed more improvement than older patients (> 50 years of age). Revision surgery resulted in similar rates compared to the original procedures.…”
Section: Surgical Treatmentmentioning
confidence: 98%